Development of BioMAP Screening for the Classification and Discovery of Natural Product Antibiotics - Wong, Weng Ruh (Chem Biol, 2012)
Despite recognition of the looming antibiotic crisis by healthcare professionals, the number of new antibiotics reaching the clinic continues to decline sharply. This study aimed to establish a new antibiotic profiling strategy using a panel of clinically relevant bacterial strains to create unique biological fingerprints for all major classes of antibiotics. BioMAP screening has been shown to effectively cluster antibiotics by structural class based on these fingerprints. Using this approach we have accurately predicted the presence of known antibiotics in natural product extracts and have discovered a novel naphthoquinone-based antibiotic from our marine natural products library that possesses a unique carbon skeleton. We have demonstrated that bioactivity fingerprinting is a successful strategy for profiling antibiotic lead compounds, and that BioMAP can be applied to the discovery of new natural product antibiotics leads.